DIAGNOSTIC VALUE OF ULTRASOUND COLOR DOPPLER MAPPING IN EARLY DETECTION OF BREAST CANCER - E. A. Busko; V. V. Semiglazov; A. V. Mishchenko; A. S. Shishova; V. O. Smirnova; E. V. Kostromina; A. V. Chernaya; A. S. Artemieva; P. V. Kryvorotko (Сибирский онкологический журнал, 2020)
Background. Experimental data suggest that tumor growth depends on angiogenesis. Once the tumor reaches a size of up to a 1 mм in diameter, a further increase in the population of tumor cells requires the growth of new blood vessels. In contrast to benign lesions, a rapid growth of cancer cells results in the formation of pathological vessels of different diameter and chaotic distribution. therefore, determination of the type of vascularization of lesions is an important criterion in the diagnosis of breast cancer (Bc). color Doppler mapping (cDM) is an ultrasound technology that evaluates blood floor through a blood vessel; however, according to data from a variety of literature sources, cDM is not sensitive to slow (week) blood flow as it allows the visualization of only large vessels with a diameter of at least 100 µm. The purpose of the study was to evaluate the diagnostic value of cDM in determining the type of vascularization of malignant and benign breast tumors, as well as to detect their statistically significant Doppler characteristics by comparing with histological findings. material and methods. From 2017 to 2019, a total of 277 women with complaints of breast lump or pain underwent ultrasound examination using cDM. Results. statistically and diagnostically significant us characteristics of benign lesions included the presence of avascular or hypovascular types of blood flow. the most significant characteristic of malignant lesions was the presence of hypervascular mixed blood flow. the diagnostic value of ultrasound B-mode in combination with cDM in differential diagnosis of breast tumors was as follows: 77.6 % sensitivity, 51.7 % specificity and 58.8 %. accuracy. Conclusion. statistically and diagnostically significant signs observed by cDM allow one to use this ultrasound technology in the early diagnosis of breast cancer. However, low diagnostic efficiency of cDM dictate the need to search for new ultrasonic signs.